2012
DOI: 10.1096/fj.12-218479
|View full text |Cite
|
Sign up to set email alerts
|

A natural point mutation changes both target selectivity and mechanism of action of sea anemone toxins

Abstract: APETx3, a novel peptide isolated from the sea anemone Anthopleura elegantissima, is a naturally occurring mutant from APETx1, only differing by a Thr to Pro substitution at position 3. APETx1 is believed to be a selective modulator of human ether-á-go-go related gene (hERG) potassium channels with a K(d) of 34 nM. In this study, APETx1, 2, and 3 have been subjected to an electrophysiological screening on a wide range of 24 ion channels expressed in Xenopus laevis oocytes: 10 cloned voltage-gated sodium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 46 publications
4
101
0
Order By: Relevance
“…On the basis of the presence of the basic-aromatic toxin surface patch it has been suggested that APETx2 may bind as PcTx1 to the acidic pocket (Baron et al, 2013). APETx2 is not selective for ASICs and inhibits voltage-gated Na + currents in DRG neurons with an IC 50 of 2.6 mM, recombinant Na v 1.8 (IC 50 of 55 nM or 19 mM, depending on the study), and Na v 1.2 (IC 50 of 114 nM) (Blanchard et al, 2012;Peigneur et al, 2012).…”
Section: Pharmacologymentioning
confidence: 99%
“…On the basis of the presence of the basic-aromatic toxin surface patch it has been suggested that APETx2 may bind as PcTx1 to the acidic pocket (Baron et al, 2013). APETx2 is not selective for ASICs and inhibits voltage-gated Na + currents in DRG neurons with an IC 50 of 2.6 mM, recombinant Na v 1.8 (IC 50 of 55 nM or 19 mM, depending on the study), and Na v 1.2 (IC 50 of 114 nM) (Blanchard et al, 2012;Peigneur et al, 2012).…”
Section: Pharmacologymentioning
confidence: 99%
“…The structure of APETx2 consists of a compact hydrophobic core composed of a four-stranded β-sheet containing three disulfide bonds, resembling a defensin-like fold ( Figure 2B & 3D) (Chagot et al, 2005;Jensen et al, 2014). At higher concentrations APETx2 also inhibits the voltage-gated sodium channels Na V 1.2, Na V 1.6, and Na V 1.8 with varying degrees of potency depending on subtype and study (Blanchard et al, 2012;Peigneur et al, 2012). Additional off target effects have been shown with APETx2 also inhibiting the cardiac hERG channel in the low micromolar range (Jensen et al, 2014), demonstrating that this prototypical "selective" ASIC3…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The MitTx identified from the venom of the Texas coral snake does not inhibit but potently activates several homomeric and heteromeric ASIC channels and helped to identify a role for peripheral ASIC1a-containing channels in cutaneous pain (13) and to define the structure of the open state of ASIC1a (14). The sea anemone toxin APETx2, a peptide that blocks ASIC3-containing channels (15) and inhibits to some extent Nav1.8 voltage-dependent Na ϩ channels (16,17), has been used to demonstrate the role of peripheral ASIC3-containing channels in acidic, inflammatory, and postoperative pain (18 -20).…”
mentioning
confidence: 99%